The Philosophy of Goroh Nguripi Sengkuni in a Javanese View - Mukti, muh mukti (Asian Journal of Philosophy and Religion, 2024)
Sengkuni's goroh nguripi philosophy stretched throughout his life from birth to death. This article will try to: 1. describe Sengkuni's goroh nguripi philosophy which stretched throughout his life from birth to death, 2. describe Sengkuni's goroh nguripi philosophy which stretches throughout his life from birth to death from the Javanese perspective. This type of research is qualitative-interpretive, the object is the story of Sengkuni's life journey from birth to death. To obtain Sengkuni's goroh nguripi philosophy which stretches across his life from birth to death, it is carried out by means of general interpretation which is based on: consistent, coherent, systematic and tested for its truth.The result: 1. Sengkuni's goroh nguripi philosophy, which stretched throughout his life from birth to death, was a deceptive behavior that brought prosperity, but there was a party that was harmed, namely the Pandavas. 2. Sengkuni's goroh nguripi philosophy, which stretches throughout his life from birth to death, in the Javanese view, is bad, aka not good (deadly lie).